LACHT association with hypoplasia of the upper airway. Clinical case (2017)
Introduction: The Mardini-Nyhan or LACHT association is a clinical condition of low prevalence that presents with pulmonary, cardiac and limb abnormalities, in which genetic etiology is not clearly documented to date. Objective: To describe the case of a 4-month-old child and the literature review of cases reported on this association, with the purpose of exposing the alterations found and thus guide the early diagnosis of this entity. Clinical case: 4 months old girl, who admitted to intensive care in mixed respiratory failure, with pulmonary, cardiac and limb disorders that meet criteria for LACHT association, additionally documents hypoplasia of the upper airway, which worsens the evolution, increases the difficulty in mechanical ventilation and favors the fatal outcome at 7 days of hospitalization. Conclusions: LACTH association is a rare pathology in which the clinical findings make it possible to suspect the diagnosis, this is the first case diagnosed in the Americas and the number 11 case in the world literature and brings as a new finding the association with hypoplasia of the upper airway. © 2017, Sociedad Chilena de Pediatria. All rights reserved.